Penerapan Manajemen Resiko Pada Rekam Medis Elektronik di Rumah Sakit Hidayah Boyolali - Nugraheni, Sri Wahyuningsih; Nopita Cahyaningrum (Jurnal Pengabdian Bidang Kesehatan, 2024)
The implementation of electronic medical records at Hidayah Boyolali Hospital from January 2023 until now is not free from risks. The risks that generally occur are incomplete filling out of electronic medical records due to doctors' indiscipline in filling out patient treatment histories, inappropriate access to medical record information due to errors in patient identification, and errors in coding patient diagnoses which cause difficulties in claims and inappropriate service financing. The aim of PkM is to increase the knowledge and skills of medical record officers regarding hybrid medical record risk management. The PkM stages are: (1) preparation and licensing, (2) presentation of material and case studies, and (3) evaluation. The results of PkM are increased knowledge and ability to identify risks, assess risks, and treat risks in hybrid medical records. Implementation of risk management is carried out in the patient registration unit, patient data processing unit, patient data storage unit, and medical information release unit.